2005
DOI: 10.3168/jds.s0022-0302(05)72669-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod During the Dry Period on Prolactin, Prolactin Receptor, and Milk Production of Dairy Cows

Abstract: Cows exposed to short day photoperiod during the dry period produce significantly more milk in their subsequent lactation than cows exposed to long days. The mechanism(s) underlying this effect are unknown. Because concentrations of prolactin (PRL) in circulation are consistently affected by changes in photoperiod, we hypothesized that alterations in the prolactin axis and sensitivity of the mammary gland to prolactin signaling may mediate photoperiodic effects in dry cows. The objective of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 25 publications
12
88
1
2
Order By: Relevance
“…Miller et al (2000) observed that the milk yield of animals exposed to shortdays in the dry period was 3.2 kg/day higher than those exposed to long-days. Prolactin plasma level was similar in short-and long-days-exposed cows during the dry period, but during lactation, cows exposed to short-days showed lower prolactin plasma level, and consequently, a higher number of prolactin receptors through the next lactation (Auchtung et al, 2005;Wall et al, 2006). Similar results were also obtained in goats (Mabjeesh et al, 2007).…”
Section: Photoperiodsupporting
confidence: 86%
“…Miller et al (2000) observed that the milk yield of animals exposed to shortdays in the dry period was 3.2 kg/day higher than those exposed to long-days. Prolactin plasma level was similar in short-and long-days-exposed cows during the dry period, but during lactation, cows exposed to short-days showed lower prolactin plasma level, and consequently, a higher number of prolactin receptors through the next lactation (Auchtung et al, 2005;Wall et al, 2006). Similar results were also obtained in goats (Mabjeesh et al, 2007).…”
Section: Photoperiodsupporting
confidence: 86%
“…However, regulation of PrlR expression and its affinity for Prl may counteract variations in plasma Prl concentrations, and the quantitative expression of PrlR may be a major determinant in Prl bioactivity. In dry dairy cows, a short-day photoperiod results in reduced plasma Prl, but increased PrlR gene expression and PrlR affinity for Prl (Auchtung et al, 2005). Low feeding level results in lower plasma Prl (Lacasse et al, 1994), and a greater gene expression of Prl receptors in cows on low feeding level may counterbalance a low Prl plasma concentration.…”
Section: Feeding Levelmentioning
confidence: 99%
“…In mammals, the hormone prolactin (PRL) is best known for its role in the regulation of lactation (Bole-Feysot et al 1998;Auchtung et al 2005;Lee et al 2007). Recent evidence indicates that PRL affects multiple reproductive and metabolic functions via the JAK2/STAT (Janus kinase 2/signal transducer and activator of transcription) signaling pathway (Clevenger and Kline 2001;Bachelot and Binart 2007).…”
Section: Introductionmentioning
confidence: 99%